Penggunaan Media Instagram @Nahwu_Pedia dalam Mahārah Al Qira’ah dan Mahārah Al Kitabah Mahasiswa Bahasa Arab - Salimatul Fuadah (Universitas Yudharta Pasuruan, 2020)
This study aims to open new innovations for online learning period in Mahārah al Qira’ah and Mahārah al Kitabah learning for arabic language students. The Instagram which has been only for posting photos, both fascinating and unique benefit stories and videos have creatived, effectively used as a learning medium for Mahārah al Qira’ah and Mahārah al Kitabah. Shows a positive response from students on the use of Instagram media. Researcher focused on using the Instagram account @Nahwu_Pedia which contains mufrodzat, mahfudzot and Qowaid Nahwu. Research method uses descriptive qualitative, with data gathered through observation, interviews and documentation. The study showed the results indicate that the @Nahwu_Pedia Instagram account media is very interesting and the material posted is very easy to understand, so that students are motivated and find it easier to hone their Mahārah al Qira'ah and Mahārah al Kitabah learning. Inadequate in the Mahārah al Qira’ah and Mahārah al Kitabah learning only uses the material in the account, if wanting to follow the learning has to learn from existing materials, and wants to learn by following the online handouts from @Nahwu_Pedia.